2008
DOI: 10.1176/ps.2008.59.9.965
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders Among Detained Youths: A Comparison of Youths Processed in Juvenile Court and Adult Criminal Court

Abstract: Community and correctional systems must be prepared to provide psychiatric services to youths transferred to adult criminal court and especially to youths sentenced to prison. When developing and implementing services, psychiatric service providers must also consider the disproportionate representation of individuals from racial-ethnic minority groups in the transfer process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
0
26
0
3
Order By: Relevance
“…Los grupos de trastornos más prevalente fueron aquellos asociados al consumo de sustancias de abuso y los trastornos disruptivos. Ambos resultados son confirmados por la literatura revisada 3,7,13,14,24 . Algunas diferencias entre los estudios pueden explicarse principalmente por dos razones: i) uso de distintos instrumentos diagnósticos, y ii) la muestra analizada en este estudio incluyó a sujetos cumpliendo condena en recintos semicerrados y abiertos, población que no siempre ha sido incluida en otros trabajos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Los grupos de trastornos más prevalente fueron aquellos asociados al consumo de sustancias de abuso y los trastornos disruptivos. Ambos resultados son confirmados por la literatura revisada 3,7,13,14,24 . Algunas diferencias entre los estudios pueden explicarse principalmente por dos razones: i) uso de distintos instrumentos diagnósticos, y ii) la muestra analizada en este estudio incluyó a sujetos cumpliendo condena en recintos semicerrados y abiertos, población que no siempre ha sido incluida en otros trabajos.…”
Section: Discussionunclassified
“…Esto sería consistente con otros estudios revisados 3,10 . De la misma manera, también existe una alta comorbilidad en trastornos relacionados al uso de sustancias, donde 47,4% de los individuos evaluados tienen dependencia o abuso a dos o más sustancias, lo que coincide con otras investigaciones 24 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…If a child or adolescent does have one of these difficulties, it most often is a singular experience (Mallett, 2003 , 2010). However, reviews of detained and incarcer ated youthful offenders have found significantly higher incidences of these experiences within this population -from two (some mental health disorders) to as many as 60 times (for maltreatment victimiza tion, see Table 4) the rates found in the child and adolescent population (Leone & Weinberg, 2010;Mears & Aron, 2003;Teplin et al, 2006;Washburn et al, 2008). Maltreatment victimization rates are the substantiated cases of abuse and neglect as reported by the U.S. Department of Health and Human Services; learning disabilities and emotional disturbances are the identified students who are under an individualized education plan as directed by the Individuals with Disabilities Education Act (U.S. Department of Education, 2010); and mental health/substance abuse disorders are diagnosed psychiatric problems as defined by the Diagnostic and Statistical Manual of Mental Health Disorders (American Psychiatric Association, 2000).…”
Section: Serious Youthful Offender Profile: Required Mitigating Evidencementioning
confidence: 97%
“…In a similar review of a jurisdiction's mental health system and juvenile court, 20% of adolescents receiving mental health services had a recent arrest record, while 30% of adolescents arrested received mental health services (Rosenblatt et al, 2000). And in a study of the mental health problems of adolescents transferred from the juvenile to the criminal courts in Chicago, over 43% of the youthful offenders had two or more psychiatric diagnoses (Washburn et al, 2008).…”
Section: Comorbiditymentioning
confidence: 99%